Analisis Pengaruh Etika Kerja Islam dan Core Values AKHLAK BUMN terhadap Kinerja Karyawan BSI: Studi Kasus BSI Corporate University - Ariqah Ghina Hasnaputri; Yunizar Yunizar (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
As the center for employee competency development, BSI Corporate University (BSU) plays a crucial role in strengthening BSI’s competitiveness within Indonesia’s rapidly growing Islamic banking industry. BSU’s performance from 2021 to 2023 experienced fluctuations, indicating the need for an evaluation of factors influencing employee performance. Previous studies have also shown inconsistent findings regarding the influence of Islamic Work Ethics and AKHLAK core values on performance, thereby creating a research gap. This study aims to examine the influence of Islamic Work Ethics and AKHLAK core values on employee performance at BSU. Data were collected through a quantitative survey of BSU employees, resulting in 60 valid responses, and analyzed using SmartPLS 4.1.1.2. The research employed a descriptive quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) as the analytical technique. The findings indicate that Islamic Work Ethics and AKHLAK core values have a positive and significant influence on employee performance.